Karakteristik desain ruang terbuka hijau pada sempadan sungai perkotaan - Kusriantari Fenny Aprillia; Titieandy Lie; Chairul Saputra (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Characteristics of green open space design on urban river borders The design of green open space on the urban river border should be able to fulfill ecological and social functions like other types of green open space. Green open space of Teras Cikapundung, green open space of Jaletreng River Park, and green open space of Taman Kaulinan have their design characteristics in realizing both functions. This study aims to uncover the characteristics of green open space design on the urban river border. The method used is descriptive qualitative. The analysis shows that the three objects of research have similarities and differences that complement each other to fulfill ecological and social functions. Ecological functions can be fulfilled well in the green open space of Teras Cikapundung and green open space of Jaletreng River Park, while the social services can be performed well in the all three green open spaces. The conclusion obtained, i.e. (a) in terms of ecological functions and social functions must be fulfilled in a balanced manner, (b) because it is located in the river border area, it is expected that the river can be used as a potential in fulfilling ecological and social functions, (c) the river border area is maintained its natural area so that animal habitat can be managed, but can be integrated with artificial areas such as reinforcement to prevent erosion and river sedimentation, (d) the river body can be used as a visitor attraction Namely by designing a sitting space facing the river, developing a circulation area along the river border, and holding river games. © 2020 Kusriantari Fenny Aprillia, Titieandy Lie, Chairul Saputra